Answer:
- 15
Step-by-step explanation:
12-4=8 which means 12-8=4 which means now you have the difference of 4 and 8+4=12 which means now you have the sum of 12
Answer:
x = 6
Step-by-step explanation:
Add the system of equations together:
2x - 3y = 12
4x + 3y = 24
you get
6x = 36
divide by the coefficient
6x/6 = 1
36/6 = 6
x = 6
Not sure if you need the y, but if so, let me know!
Hope this helps!
Answer:
B - y = 2x - 8
Step-by-step explanation:
Step 1: find slope
2x + 4y = 6
4y = -2x + 6
Make y the subject of the formula
y =( -2x + 6)/4
We can separate to get the slope
y = -2x/4 + 6/4
y = -x/2 + 3/2
Slope m = -1/2
Step 2: using a point slope form equation
y - y1 = m ( x - x1)
Note: if two lines are perpendicular to the other, it is always a negative reciprocal of each other
ie m = 2
Substitute m into the equation
y - y1 = 2(x - x1)
Step 3: sub the point
( 6 , 4)
x1 = 6
y1 = 4
y - 4 = 2( x - 6)
Step 4 : using a slope intercept form equation
Open the bracket
y - 4 = 2x - 12
y = 2x - 12 + 4
y = 2x - 8
The equation of a line is
y = 2x - 8
Answer:
option D
2x − 7(−3x − 17) = 4
Step-by-step explanation:
Given in the question two equations
<h3>Equation 1</h3>
2x - 7y = 4
<h3>Equation 2</h3>
3x + y = -17
Rearranging equation 2 in terms of y
3x + y = -17
y = -17 - 3x
Put this value of y in Equation 1
2x - 7y = 4
2x - 7(-17 - 3x) = 4
So,
If you use the substitution method to solve the following system, new equation will be
<h3>2x - 7(- 3x - 17) = 4 </h3>